Dialogue about BNCC, the curriculum and its interference For teacher training - Souza, Sawana Araújo Lopes de; Sousa, Maraiane Pinto de; Aragão, Wilson Honorato (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The BNCC is configured as a curricular proposal that directs the states and municipalities to reformulate and reframe the curricula. This includes the initial and continuing training of basic education teachers, since the LDB (9.394 / 96) presents as a category of curricular adequacy to the BNCC. The present work aims to analyze the references presented in the BNCC for the implementation of the new curricula with regard to teacher training. Thus, it has as a problem: how the dialogue at BNCC is being built between the curriculum and the training of teachers. Methodologically, this is a research with a qualitative and documentary approach. We conclude that this document serves as a parameter to understand how teacher education is conceived in the light of the Base, since professionals in basic education will be the protagonists in the dynamics of the curriculum within the classroom.